Pengaruh Motivasi Berprestasi dan Prestasi Akademik terhadap Kemampuan Pemecahan Masalah Kewarganegaraan - Yunus, Muhammad; Habibi, Muhammad Mujtaba; Mawarti, Rista Ayu (Universitas Negeri Malang, 2020)
This study aimed to determine the effect of motivation achievement and academic achievement on citizenship problem-solving. This study used a quantitative approach to the type of correlational research. The research population was 704 students of State University of Malang, namely students which were taking Civics Education courses in the even semester of the academic year 2018/2019. The sample consisted of 70 students that were chosen by a purposive random sampling technique. Data collection was done by questionnaire, documentation, and essay test. Questionnaires were used to measure achievement motivation, documentation was used to obtain academic achievement data, and essay tests to measure problem-solving abilities. Data analysis used multiple regression with the SPSS application. The results of the study indicated that achievement motivation influenced the ability to solve citizenship problems. Academic achievement affected the ability to solve citizenship problems. Simultaneously, achievement motivation and academic achievement together affected the ability to solve citizenship problems.